2014
DOI: 10.1007/s00210-014-1034-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic overview of systemic chlorogenic acid therapy on experimental wound healing

Abstract: Chlorogenic acid (CGA) is a well-known natural antioxidant in human diet. To understand the effects of CGA on wound healing by enhancing antioxidant defense in the body, the present study sought to investigate the potential role of systemic CGA therapy on wound healing and oxidative stress markers of the skin. We also aimed to understand whether chronic CGA treatment has side effects on pivotal organs or rat bone marrow during therapy. Full-thickness experimental wounds were created on the backs of rats. CGA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 71 publications
3
33
0
Order By: Relevance
“…The peroxynitrite is capable of initiating lipid peroxidation, inflammation, cancer, and other pathological condition (Bates, Baker, Guerra, & Harrison, ). The observed results from this finding also agree with other studies on the inhibitory effects of caffeic acid and chlorogenic acid on MDA level and their anti‐inflammatory effects during wound healing in experimental animals (Bagdas et al, ; Gul, Demircan, Bagdas, & Buyukuysal, ). Furthermore, as revealed in Figure , caffeic and chlorogenic acid also exhibit NO radical scavenging ability, which can prevent peroxynitrite formation, reduce the potential for lipid peroxidation in the heart, and protect the heart membrane integrity.…”
Section: Discussionsupporting
confidence: 92%
“…The peroxynitrite is capable of initiating lipid peroxidation, inflammation, cancer, and other pathological condition (Bates, Baker, Guerra, & Harrison, ). The observed results from this finding also agree with other studies on the inhibitory effects of caffeic acid and chlorogenic acid on MDA level and their anti‐inflammatory effects during wound healing in experimental animals (Bagdas et al, ; Gul, Demircan, Bagdas, & Buyukuysal, ). Furthermore, as revealed in Figure , caffeic and chlorogenic acid also exhibit NO radical scavenging ability, which can prevent peroxynitrite formation, reduce the potential for lipid peroxidation in the heart, and protect the heart membrane integrity.…”
Section: Discussionsupporting
confidence: 92%
“…Chlorogenic acid and quercitrin were also shown to have wound healing potential. 50,51 Our results and the data in the literature show that phenolic compounds may have important role in the wound healing potential of Hypericum genus. Study limitations Crude methanolic and aqueous extracts of H. pseudolaeve were investigated for their in vitro wound healing activity, antioxidant activity and phytochemical content.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 57%
“…The reduction of inflammation resulting in enhanced wound healing has also been reported for CGA in different studies [111]. In a study with diabetic rats, the oral administration of 5-CQA enhanced hydroxyproline and decreased malondialdehyde/nitric oxide levels in wound tissues, in addition to elevating reduced-glutathione [143,144]. Another in vivo study using a mice skin excision wound showed that topically administrated hydrogels containing 5-CQA reduced significantly the wound area size in the inflammatory phase, enhancing the wound healing process [145].…”
Section: Anti-inflammatory Effect and Wound Healingmentioning
confidence: 55%
“…In both cases, suppression of pro-inflammatory cytokines was observed. CGA (5-CQA) could effectively prevent mice from concanavalin A-induced hepatitis, which might have resulted from the activation of Toll-Like Receptor (TLR) 4 signaling, downregulating the expression of adhesion molecules, and also alleviating the infiltration and activation of hepatic leukocytes and the production of pro-inflammatory cytokines [143].…”
Section: Anti-inflammatory Effect and Wound Healingmentioning
confidence: 99%